Taṭwīru Wasāʾili Al-Biṭāqati Al Muṣawwarah ʿalā Naẓariyyati Al Tarmīzi Al Muzdawaj Li Tarqiyati Al Mufradāti Al-Lughati Al ʿarabiyyah - Rohmatun Nurul Hidayah; Ni’matul Khoiriah (STIQ Amuntai, 2026)
This study aims to develop flashcard learning media based on dual coding theory to improve Arabic vocabulary mastery in beginner students. This study uses a research and development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The study was conducted on beginner students at the Sa'diyah Dormitory, Sunan Drajat Islamic Boarding School, Lamongan. Data collection techniques used observation, interviews, documentation, and tests. Data analysis was descriptive, and the effectiveness test used a t-test. The study's results showed that the developed flashcard media had a very high level of feasibility, with 96% from material experts and 95% from media experts. The effectiveness test showed a significant increase in students' Arabic vocabulary mastery, as evidenced by the t-test results, with a calculated t value (8.747) > t table (2.069). The use of flashcards in learning increased students' attention, motivation, and active participation in the Arabic vocabulary learning process. In addition, the effectiveness test results showed an increase in vocabulary mastery after using dual-coding-based flashcard media. Thus, flashcard media based on dual coding theory is considered feasible and effective as a learning medium for improving Arabic vocabulary mastery among beginner students.